Teleconsultation in the Portuguese National Health Service During the COVID-19 Pandemic: A Survey of Physicians’ Views and Future Implications - O'Neill, Catarina (2022)
Introduction: The COVID-19 pandemic led to the reorganization of healthcare services and teleconsultation emerged as a solution to facilitate patient appointments. The aim of this study was to characterize, from a physician perspective, the teleconsultations carried out in the Portuguese National Health Service (SNS) during the first phase of the pandemic and to identify factors that influence the experience of the teleconsultation.Material and Methods: A cross-sectional analytical study was conducted based on an online survey, between July-September 2020, aimed at SNS doctors. Data on demographics, practice, attitudes and perceptions associated with the teleconsultation was collected. The adjusted prevalence ratio (aPR) was calculated to identify demographic factors and determinants of teleconsultation associated with satisfaction, use of video calls and greater motivation to carry out teleconsultations in the future.Results: 2225 valid responses were obtained. Teleconsultation was carried out by 93.8% of participants in this period, 99.0% used the telephone as a form of communication and only 8.0% used a video call. A high degree of satisfaction with the teleconsultation was significantly associated with perceiving the teleconsultation as providing care with equivalent quality to a face-to-face consultation (aPR = 1.472) and being motivated to do teleconsultation after the pandemic (aPR = 4.081). Reporting clinical (aPR = 0.763) or technical difficulties (aPR = 0.666) was negatively associated with satisfaction. 70.4% of doctors would like to continue doing follow-up teleconsultations and 53.3% consider that video call technologies should always or often be used during teleconsultations.Conclusion: Teleconsultation seems to have potential to become a common practice in the future. However, it is important to address clinical, technical, organizational, and legal questions and, above all, to ensure that it is a safe and valuable practice for patients.